Strengthening Awareness of Religious Moderation Through ‎Podcast Media - Yusuf, Achmad (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
This research analyzes the effectiveness of the Thematic Real Work Lecture Program (KKN-T) at Yudharta Pasuruan University in Jatisari Village, Purwodadi, Pasuruan, in strengthening awareness of religious moderation through the use of podcasts as a discussion platform. Aims to understand the impact of community participation in creating podcast content and measure the success of using podcasts in increasing awareness of religious moderation in the local environment.